The Influence Of Human Resource Management In Increasing Visitor Satisfaction At The Sultan Agung Banjarbaru Islamic Hospital - Junaidi Junaidi; Amalia Wahyuni (International Journal of Economics, Management and Accounting, 2024)
This study aims to examine: about the function of Human Resource Management (HRM) in a company in increasing customer satisfaction, especially for patients at Sultan Agung Islamic Hospital Banjarbaru. The research design is a qualitative research which is a type of field survey research and a type of research whose findings are not obtained through statistical procedures or other forms of calculation. The results showed that human resource management is very influential on the satisfaction of visitors or patients at the Islamic Hospital Sultan Agung Banjarbaru, the results of the study obtained from several dimensions, namely: reliability, responsiveness, assurance, empathy, physical appearance. And from these results indicate that the informants are not satisfied with the dimensions of reliability, responsiveness, empathy and physical appearance due to queuing problems, health workers do not provide good explanations and understanding, doctors pay less attention when providing services. Meanwhile, informants who are satisfied only with the guarantee variable because the service they get is very good and the doctor is able to assure the patient's recovery, provides a sense of security, is friendly, polite and gentle.